Sistem Tanda Sebagai Media Informasi Komplek Sarana Olahraga Dadaha Kota Tasikmalaya - Satria, Alief Ananda (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2023)
The Dadaha Sports Facilities Complex, Tasikmalaya City, is the center of sports activities for the residents of Tasikmalaya City and its surroundings. The complete facilities make this place always busy with visitors from morning to evening. The area of ​​the Dadaha Sports Facilities Complex is around 16 hectares. The facilities available include a sports hall (GOR), swimming pool, sports field, archery, fitness center and others. Apart from that, the Dadaha Sports Facilities Complex also has a park and children's play area. However, in a place this large, there is still a lack of information systems, such as the absence of regulations not to litter, so there is a lot of rubbish scattered in the park, and the existing sign system is less visible because the color is dark and the writing is too small. Apart from that, there are several public facilities that do not have an identity, for example public toilets. Therefore, the designer hopes that in preparing this report he can solve and improve this problem by designing a complete sign system with a visual concept for the sign system which will be taken from several characteristics of the City of Tasikmalaya.